Man continues to climb Gunung Rajah despite brush with death - UMP, . (The New Straits Times Press (M) Bhd, 2015)
Bentong: Despite being struck by lightning while hiking up Gunung Rajah 11 years ago, Muhammad Sobri Zainal continues to help hikers climb the mountain